Upaya Guru Pendidikan Agama Islam Dalam Mengatasi Kesulitan Membaca Al-Qur’an Di Sekolah Menengah Atas - Damanhuri, Damanhuri; Bunayar, Bunayar; Hamzah, Iri; Zunarti, Rita; Muhlisa, Muhlisa; Asy'arie, Bima Fandi (LP2M Universitas Islam Ahmad Dahlan, 2025)
This research aims to describe PAI teachers' efforts to overcome difficulties in reading the Qur’an and knowing the factors behind students’ finding it difficult to read the Qur'an. This research focuses on SMA Negeri 2 Sape, Bima Regency. This research is field research; the type used is a case study with a qualitative approach. The data obtained in this research were from 52 participants. The data follows: PAI teachers' efforts have used the habituation method. For example, the teacher reads first, then the students follow, providing tutors (coaches) and giving motivation, and the method used to teach students to read the Qur’an is the Iqro' method. Second, internal factors are a lack of motivation from parents, a lack of awareness of oneself, and the influence of technological developments. Then, external factors include a lack of interest, talent, and passion, a lack of practice in learning to read the Qur’an, and wrong social interactions in the environment.